THE EFFECT OF LEARNING CONTRACTS ON STUDENTS' DISCIPLINE ATTITUDES IN THE HISTORY SUBJECT OF GRADE X AT SMAN 2 RENGAT BARAT: PENGARUH KONTRAK BELAJAR TERHADAP SIKAP DISIPLIN PESERTA DIDIK PADA MATA PELAJARAN SEJARAH KELAS X DI SMAN 2 RENGAT BARAT - Ahmal; Asril; Putri (SOSIOEDUKASI, 2025)
In Education needed the name fun learning , active students , creative teachers​ And peaceful class . In a learning process required interest participant educate the class more felt life , especially in learning History . In learning History is a eye Less lessons learned in demand by sises , by because that teacher must clever in interesting attention students . If student No interested And feel osan , of course  will influential towards the level of demand , and sense of discipline they . By because That in study This will be explained What is the level of discipline ? student in learning History in the classroom X SMAN 2 West Rengat .